2019
DOI: 10.1108/ijmpb-07-2018-0128
|View full text |Cite
|
Sign up to set email alerts
|

Strategy development using TOWS matrix for international project risk management based on prioritization of risk categories

Abstract: Purpose International projects very commonly experience failure due to various factors at the global level. Especially, large projects at the international level virtually have no chance of meeting scope, time, cost and quality. This fact has been underlined by most of the international surveys and published literature. Effective risk management plays a vital role in preventing projects from failure by implementing appropriate risk response strategies. The success of risk management will be based on the unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 96 publications
(62 reference statements)
1
45
0
Order By: Relevance
“…Motivating and engaging employees in green initiatives results in improved performance and higher customer satisfaction (Srivastava and Shree, 2019; Zaid et al , 2018). Management support and rewards to the employees (Dandage et al , 2019; Guerci et al , 2016) for their initiatives in reducing pollution or waste management motivates them further to participate in trainings and take new initiatives for geen upply chain. Success of engaging employees in green initiatives depends majorly on the skills of employees and their willingness to work for new designs and products considering environment impacts (Sancha et al , 2016, Kumar and Rahman, 2015).…”
Section: Literature Surveymentioning
confidence: 99%
“…Motivating and engaging employees in green initiatives results in improved performance and higher customer satisfaction (Srivastava and Shree, 2019; Zaid et al , 2018). Management support and rewards to the employees (Dandage et al , 2019; Guerci et al , 2016) for their initiatives in reducing pollution or waste management motivates them further to participate in trainings and take new initiatives for geen upply chain. Success of engaging employees in green initiatives depends majorly on the skills of employees and their willingness to work for new designs and products considering environment impacts (Sancha et al , 2016, Kumar and Rahman, 2015).…”
Section: Literature Surveymentioning
confidence: 99%
“…The bibliographic research in the field of risk management in international projects and teams in the virtual environment revealed that the research undertaken was very scarce [7] and focused on specific phases of the risk management process, mainly, on identifying and analyzing risks in international projects [4,28] especially those in the field of construction [8,15,30,31,32] or within dispersed teams in software projects [11,29,33,34,35] and to a very small extent, virtual project teams [18,36].…”
Section: Theoretical Framework For Risk Management In Iptvementioning
confidence: 99%
“…International projects very often face failure due to different and complex factors globally. In particular, large international projects are very unlikely to meet the scope, time, cost and quality [4]. Hubbard [5] (p. 7) claims that the ultimate common mode failure would be a failure of the risk management process itself.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kirkire et al (2018) implemented PRM practices in a dental-product-manufacturing company for MPD. (Dandage et al , 2019) used interpretive structural modeling and Matrice d’Impacts Croisés Multiplication Appliqués à un Classement for risk prioritization in international projects. Rane et al (2019) developed a PRM framework based on Industry 4.0 technologies and demonstrated the developed framework using IoT technology.…”
Section: Literature Surveymentioning
confidence: 99%